2006
DOI: 10.1158/0008-5472.can-06-1019
|View full text |Cite|
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor–Related Protein Inhibits Cell Growth and Invasion in Pancreatic Cancer

Abstract: The epidermal growth factor receptor (EGFR) signaling network plays critical roles in human cancers, including pancreatic cancer, suggesting that the discovery of specific agents targeting EGFR would be extremely valuable for pancreatic cancer therapy. EGFR-related protein (ERRP), a recently identified pan-erbB inhibitor, has been shown to inhibit growth and induce apoptosis of pancreatic cancer cells in vitro and tumor growth in a xenograft model. However, the precise molecular mechanism(s) by which ERRP exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…Fifth, hypoxia-driven upregulation of c-Met seems to contribute to the invasive front in PDAC (40). Taken together, these observations suggest that ligation In the present study, we showed that COLO-357 cells, which express very low levels of endogenous Np-1, were not able to exhibit increased invasiveness in the presence of HGF although these cells are capable of responding to EGF (41) and TGF h-1 (22) with increased invasiveness. However, stable overexpression of Np-1 in these cells resulted in a marked increase in invasiveness in response to HGF, and this effect was abolished by siRNA-mediated down-regulation of c-Met.…”
Section: Cancer Researchsupporting
confidence: 51%
“…Fifth, hypoxia-driven upregulation of c-Met seems to contribute to the invasive front in PDAC (40). Taken together, these observations suggest that ligation In the present study, we showed that COLO-357 cells, which express very low levels of endogenous Np-1, were not able to exhibit increased invasiveness in the presence of HGF although these cells are capable of responding to EGF (41) and TGF h-1 (22) with increased invasiveness. However, stable overexpression of Np-1 in these cells resulted in a marked increase in invasiveness in response to HGF, and this effect was abolished by siRNA-mediated down-regulation of c-Met.…”
Section: Cancer Researchsupporting
confidence: 51%
“…The transfected cells (5 Â 10 3 ) were seeded in a 96-well culture plate and subsequently incubated with MTT reagent (1.0 mg/mL) at 37jC for 2 h, and MTT assay was performed as described earlier (16). The results were plotted as mean F SD of three separate experiments having six determinations per experiment for each experimental condition.…”
Section: Methodsmentioning
confidence: 99%
“…FoxM1 siRNA and siRNA control were obtained from Santa Cruz Biotechnology. The FoxM1 cDNA plasmid was purchased from OriGene Technologies Inc. Human PC cells were transfected with FoxM1 siRNA and cDNA, respectively, using LipofectAMINE 2000 as described earlier (16).…”
Section: Introductionmentioning
confidence: 99%